Dual-channel current valve in a three terminal zigzag graphene nanoribbon junction. (12th December 2016) - Zhang, L
Abstract: We theoretically propose a dual-channel current valve based on a three terminal zigzag graphene nanoribbon (ZGNR) junction driven by three asymmetric time-dependent pumping potentials. By means of the Keldysh Green's function method, we show that two asymmetric charge currents can be pumped in the different left–right terminals of the device at a zero bias, which mainly stems from the single photon-assisted pumping approximation and the valley valve effect in a ZGNR p - n junction. The ON and OFF states of pumped charge currents are crucially dependent on the even–odd chain widths of the three electrodes, the pumping frequency, the lattice potential and the Fermi level. Two-tunneling spin valves are also considered to spatially separate and detect 100% polarized spin currents owing to the combined spin pump effect and the valley selective transport in a three terminal ZGNR ferromagnetic junction. Our investigations might be helpful to control the spatial and spin degrees of freedom of electrons in graphene pumping devices.